Parámetros hematológicos del búfalo de agua (Bubalus bubalis) en Ecuador - Jiménez González, Marco Xavier (2021)
With the objective of characterizing the hematological and biochemical profiles of the water buffalo (Bubalus bubalis), the present investigation was carried out in order to contribute and publicize the health reality in which the species has been developing in Ecuador and its regions. of study interest, littoral or coast, inter-Andean or sierra and oriental or Amazonian. The study was developed in 84 animals in a completely randomized design (DCA) factorial (3x2x2) and an analysis of variance (p<0.05), highlighting three already specified regions of interest, two ages between 1 - 3 years and 3 - 5 years respectively and divided between the two sexes. The following general values detailed below were obtained and taking into account the (Mean±S.E.) for the biochemical profile with its variables, GLU mg/dL 55.36±1.95, CREA mg/dL 1.57±0.05 , BUN mg/dL 11.94±0.41, BUN/CREA ratio 8.42±0.4, TP mg/dL 8.18±0.17, ALB mg/dL 3.17±0.05, GLOB mg/dL 4.95±0.14, ALB/GLOB ratio 0.66±0.02, ALT U/L 91.76±3.3, ALKP U/L 180.8±15.29 with their general values for the biometric profile in its (Mean±S.E.) with its variables % HCT 35.92 ±0.7, HGB (g/dL) 12.25±0.26, MCHC (g/dL) 34.3±0, 18, # WBC K/μL 7.49±0.43, # GRAND K/μL 2.55±0.18, % GRAND 34.53±1.38, L/M x10ᶺ9/L 5.16±0, 36, % L/M 65.86±1.42, PLAQ K/μL 180.8±15.29 respectively. Hoping that the data obtained in this trial will be of practical use when carrying out an adequate clinical assessment of the animals and that they also serve as a contribution to the development of the sanitary management of the species in the country.